2011
DOI: 10.1249/mss.0b013e31821f4090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inspiratory Muscle Training on Exercise Tolerance in Asthmatic Individuals

Abstract: These data suggest that IMT attenuates inspiratory muscle fatigue, reduces the perception of dyspnea, and increases exercise tolerance. These findings suggest that IMT may be a helpful adjunct to asthma management that has the potential to improve participation and adherence to exercise training in this group. However, the perception of breathlessness is also an important signal of bronchoconstriction, and thus, caution should be exercised if this symptom is abnormally low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 39 publications
(51 reference statements)
3
34
0
6
Order By: Relevance
“…Improvement in PEFR was observed in PG only which is in agreement with the feature that the POWERbreath Plus company developed to improve the air flow [29]. Turner et al, [8] which studied the influence of IMT on exercise tolerance with asthmatic patients; it was applied on Fifteen asthmatic patients (seven males, eight females) seven as Threshold group while the other eight in the control group; and they proved that PEFR doesn't show any improvement after six weeks of training using IMT device (Training consisting of 30 breaths twice daily at 50% of MIP) and that's in harmony with our findings in Threshold group.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Improvement in PEFR was observed in PG only which is in agreement with the feature that the POWERbreath Plus company developed to improve the air flow [29]. Turner et al, [8] which studied the influence of IMT on exercise tolerance with asthmatic patients; it was applied on Fifteen asthmatic patients (seven males, eight females) seven as Threshold group while the other eight in the control group; and they proved that PEFR doesn't show any improvement after six weeks of training using IMT device (Training consisting of 30 breaths twice daily at 50% of MIP) and that's in harmony with our findings in Threshold group.…”
Section: Discussionsupporting
confidence: 77%
“…Both Souza et al, [3] and Albuquerque et al, [15] showed no change in lung volumes as stated by Enright and Unnithan [12]. In contrast, TURNER et al [8] reported that six weeks training period using PR-IMT in asthmatic patients with a moderate load of 50% improved MIP, tolerance and perception of dyspnea. But no significant changes were noted in the following pulmonary function variables: peak expiratory flow rate, forced expiratory flow, neither forced vital capacity nor forced expiratory volume during the first second.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Desde 2002, Romer e outros (14) já haviam descrito a melhora da performance de ciclistas após TMI, entretanto, repercussões em indivíduos com algum quadro patológico ainda não são tão frequentes. Tuner e outros (15) em 2013 foram um dos poucos que relataram a melhora da sensação de dispnéia em pacientes asmáticos submetidos a um protocolo de TMI.…”
Section: Discussionunclassified